Regional variety preferences by teachers in USA - Angela George; Anne Hoffman-González (Revista de Lingüística y Lenguas Aplicadas, 2023)
Spanish teachers in the USA are responsible for showing students what Spanish looks and sounds like (Ballman, Liskin-Gasparro & Mandell, 2001) and therefore act as role-models for their students in terms of their attitudes towards different varieties of Spanish. They must choose which features from which varieties to teach their students (Burns, 2018). Spanish teachers in the UK found Caribbean Spanish difficult to comprehend (Bárkányi & Fuerte Gutiérrez, 2019) and Spanish teachers in the USA preferred Peninsular Spanish over other varieties (Martínez-Franco, 2019), similar to Spanish teachers in Australia (Ortiz-Jiménez, 2019). The current study investigates (dis)preferences towards different regional varieties of Spanish by 63 primary, secondary and postsecondary teachers of Spanish in the USA. The findings indicate preferences split among four macro-varieties and a dispreference for Caribbean Spanish, highlighting the importance of comprehension and exposure to varieties regardless of prior explicit training on the topic.